Statistical Analysis of Human Body Parametersfor Determining Optimal Work and Rest Cycle - Shilpa, M.; G S Prakash,; Janhavi Kiran Palka,; Jagadish Ratkal, (Journal of Mines, Metals and Fuels, 2023)
It is a normal practice in industry to assign tasks to the workers not considering seriously the age, gender, height and other parameters of the workers. The rest breaks, overtime work, prolonged repetitive tasks are given to the workers which are not scientifically assessed depending on the worker’s health condition. Due to these reasons, the workers may experience discomfort at the workplace leading to fatigue and at later stages, reduced efficiency. There are many research works available in the literature to provide occupational safety and health measures regarding this; one such measure is scheduling of rest breaks in between the work cycle to overcome fatigue. Not much work is carried out in the literature regarding scientifically scheduling the rest breaks in Indian industrial work environment. This paper focuses on identifying and analyzing the human body parameters that are important indicators to ensure that appropriate task is assigned to the worker based on his parameters. This work scientifically assesses the human body parameters of workers individually and suggests the basis for providing optimum rest breaks to the workers. For this purpose, workers working in various industries have been asked to participate in the treadmill test and stress profiles are obtained. Using these profiles, a mathematical model is developed to obtain optimal rest schedules by considering the human body parameters